Practice as ‘Research’ Within The Context of Art and Design Academia: A Brief Excursion Into Its Philosophical Underpinnings - Dominique Rio Adiwijaya; Anita Rahardja (Humaniora, 2015)
Integration of many fields of human endeavor including art and design into academic system is not at all surprising in our modern world that continues to modernize itself in the quest for ever increasing welfare of humanity. The backbone of modern welfare is unmistakably techno-scientific academic research, explaining current expansion of its ‘standardized’ paradigm, regulation and infrastructure without exception into the field of art and design. This is where the problem precisely arises, since their own nature, art and design as ‘creative’ fields, are incompatible with scientific paradigm which emphasizes a uniform reproducibility of research findings. ‘The heart of the arts’, in contrast, is its singularities. The industry actually has recognized the difference by assigning ‘patents’ to technological invention and ‘copyright’ to singular artworks. The question is then how to incorporate such creatively plural fields into uniform academic research system. Fortunately within the past 20 years, there were developments within international art and design academia that came up with a keystone principle called practice-based research. It relies upon philosophical underpinnings of phenomenology and hermeneutics which has been critically acclaimed in showing inadequacies of positivistic (natural science-based) paradigm in understanding cultural phenomena exemplified by art and design. It is the intention of this article to briefly explain this new principle and its philosophical underpinnings in order to let us appreciate its positive contribution for our understanding of art and design. This understanding in turn would allow us to cultivate those creative fields within academic context in a more appropriate way.